Positive Effects of Probiotic Therapy in Patients with Post-Infectious Fatigue - Katharina Obermoser; Natascha Brigo; Andrea Schroll; Pablo Monfort-Lanzas; Johanna M. Gostner; Sabine Engl; Simon Geisler; Miriam Knoll; Harald Schennach; Günter Weiss; Dietmar Fuchs; Rosa Bellmann-Weiler; et al. (Metabolites, 2023)
Post-infectious fatigue is a common complication that can lead to decreased physical efficiency, depression, and impaired quality of life. Dysbiosis of the gut microbiota has been proposed as a contributing factor, as the gut–brain axis plays an important role in regulating physical and mental health. This pilot study aimed to investigate the severity of fatigue and depression, as well as the quality of life of 70 patients with post-infectious fatigue who received a multi-strain probiotic preparation or placebo in a double-blind, placebo-controlled trial. Patients completed questionnaires to assess their fatigue (fatigue severity scale (FSS)), mood (Beck Depression Inventory II (BDI-II)), and quality of life (short form-36 (SF-36)) at baseline and after 3 and 6 months of treatment. Routine laboratory parameters were also assessed, including immune-mediated changes in tryptophan and phenylalanine metabolism. The intervention was effective in improving fatigue, mood, and quality of life in both the probiotic and placebo groups, with greater improvements seen in the probiotic group. FSS and BDI-II scores declined significantly under treatment with both probiotics and placebo, but patients who received probiotics had significantly lower FSS (p < 0.001) and BDI-II (p < 0.001) scores after 6 months. Quality of life scores improved significantly in patients who received probiotics (p < 0.001), while patients taking a placebo only saw improvements in the “Physical limitation” and “Energy/Fatigue” subcategories. After 6 months neopterin was higher in patients receiving placebo, while no longitudinal changes in interferon-gamma mediated biochemical pathways were observed. These findings suggest that probiotics may be a promising intervention for improving the health of patients with post-infectious fatigue, potentially through modulating the gut–brain axis.